2015
DOI: 10.5152/tjg.2015.150199
|View full text |Cite
|
Sign up to set email alerts
|

Mallory-Denk bodies: Correlation with steatosis, severity, zonal distribution, and identification with ubiquitin

Abstract: Background/Aims: Intermediate filament proteins contain few aggregates as their main component. Among those, Mallory-Denk bodies (MDBs) are by far the best recognized component. To identify the presence of MDBs in individuals having chronic liver disease and to evaluate the correlation among MDBs and steatosis as well as the severity and zonal distribution of hepatocyte balloon degeneration. Tertiary reference hospital. Materials and Methods: Three hundred consecutive liver specimens derived from our patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…According to Brunt et al [ 48 ] grading and staging system of NASH, these experimental groups fall in grade-2 and fibrotic stage-3. The positive correlation between Mallory–Denk bodies and severity of steatosis and hepatitis was reported by Kayaçetin [ 83 ], which supports our histopathological description. In this study, use of atorvastatin showed no protective effect on histological picture of NAFLD in hypercholesterolemic rabbits, but serum transaminases maintained within normal and serum lipids (lipid profile not shown) significantly reduced; this is in line with Hyogo et al [ 63 ], who reported normalisation of serum transaminases, while the histological picture of NASH improved in some patients and got worse in some others due to progression of fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…According to Brunt et al [ 48 ] grading and staging system of NASH, these experimental groups fall in grade-2 and fibrotic stage-3. The positive correlation between Mallory–Denk bodies and severity of steatosis and hepatitis was reported by Kayaçetin [ 83 ], which supports our histopathological description. In this study, use of atorvastatin showed no protective effect on histological picture of NAFLD in hypercholesterolemic rabbits, but serum transaminases maintained within normal and serum lipids (lipid profile not shown) significantly reduced; this is in line with Hyogo et al [ 63 ], who reported normalisation of serum transaminases, while the histological picture of NASH improved in some patients and got worse in some others due to progression of fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…As a consequence, formation of MDBs can be seen not only as “morphological biomarker” associated with cellular stress and aging but also as product of accumulation of misfolded proteins, which in turn may enhance aging-related cellular responses as indicated by the p16 positivity. This establishes a new diagnostic potential of MDBs, particularly because they are independently associated with fibrosis progression and finally liver failure [ 42 44 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…In line with this point of view are recently published data concerning the protective role of the formation of large insoluble aggregates against the cellular oxidative stress 33 . Intriguingly, the TG2 crosslinking activity plays a key role in the formation of Mallory-Denk bodies (MDBs), which are protein aggregates consisting of ubiquitinated keratins characteristic of alcoholic and NASH 34 . The TG2-dependent formation of highly crosslinked MDBs is functional to their elimination via macroautophagy 20 .…”
Section: Discussionmentioning
confidence: 99%